The stain and the sign. Poetics in Philip Roth’s "The Human Stain" - Veisland, Jørgen (Adam Mickiewicz University, 2008)
The paper shows how Philip Roth’s text discards and negates language, fiction and the temporality of narrative, replacing them with an experimental poetics that inscribes form into the body itself, endowing it with sensuality and musicality and manifesting itself as a new spatio-temporal form. Drawing on Heraclitus, Kenneth Burke, Friedrich Nietzsche and the poet S. Ulrik Thomsen, the paper further demonstrates how woman is in the place of the truth, and how “truth” in a sense is “no knowledge”. The dialogue between the feminine and the masculine, and the passion between a woman and a man expands subjectivity into an Other, a Third Form tending towards formlessness and eliminating the dualism of thinking and sensing.